PROBLEMATIKA PELAKSANAAN EKSEKUSI PUTUSAN DALAM PERKARA PENYELESAIAN HUBUNGAN INDUSTRIAL DI KALIMANTAN TIMUR - Andri Pranata (ADMIN: Jurnal Administrasi Negara, 2026)
The execution of decisions of the Industrial Relations Court (Pengadilan Hubungan Industrial/PHI) constitutes a crucial stage in ensuring legal protection for both workers and employers. However, in practice, many PHI decisions that have obtained final and binding legal force are not effectively executed, resulting in legal uncertainty and substantive injustice, particularly for workers. This study aims to analyze the mechanism for executing PHI decisions, to identify the legal and non-legal obstacles to their implementation in East Kalimantan, and to formulate legal measures and solutions to overcome these obstacles. This research employs a normative legal research method with statutory, conceptual, and case approaches. The findings indicate that the absence of specific regulations governing the execution of PHI decisions under Law Number 2 of 2004 causes the execution process to rely on general civil procedural law, which is formalistic and insufficiently responsive to the characteristics of industrial relations disputes. This condition is further exacerbated by employers’ non-compliance, the transfer or absence of company assets, the weak coercive force of court decisions, and the limited role of courts at the execution stage. Therefore, it is necessary to strengthen the execution mechanism through the submission of precautionary seizure during the examination stage, the use of coercive legal measures, the enhancement of the court’s active role in the execution process, synergy between courts and labor authorities, the implementation of execution guarantee mechanisms, and the improvement of access to legal aid for workers. These measures are expected to bridge the gap between legal certainty, substantive justice, and legal effectiveness in the execution of PHI decisions.